Vibration reduction performance of an innovative vehicle seat with a vibration absorber and variable damping cushion. (March 2022) - Gao, Pu; Liu, Hui; Xiang, Changle; Yan, Pengfei
Road driving conditions are complicated, and road unevenness and speed bumps are main sources of vibration that cause the discomfort of passengers in vehicles. The vehicle seat can effectively reduce the system damage and human discomfort caused by this vibration. In this paper, an innovative damping seat that combines a vibration absorber and variable damping cushion is proposed for better vibration reduction performance under different external road excitations. A practical vertical human-seat-vehicle model is established, and uneven road excitation considering trapezoidal speed bumps and rectangular speed bumps is applied to the vertical model. The vibration reduction mechanisms of four different seats (without the absorber and variable damping cushion, with the absorber, with the variable damping cushion and with the new damping seat) are studied by comprehensive time-frequency analysis of the vibration responses. A comparison verifies the improved vibration damping performance of the newly proposed scheme, providing good theoretical guidance for the development of damping seats.